Asymptotic normality of the optimal solution in multiresponse surface mathematical programming - Díaz-García, José A. (Metodološki zvezki, 2015)
An explicit form for the perturbation effect on the matrix of regression coefficients on the optimal solution in multiresponse surface methodology is obtained in this paper. Then, the sensitivity analysis of the optimal solution is studied and the critical point characterisation of the convex program, associated with the optimum of a multiresponse surface, is also analysed. Finally, the asymptotic normality of the optimal solution is derived by the standard methods.
Keywords: Statistics; Statistika; Statistical data; Statistični podatki; Statistična analiza; Statistical analysis; matematično programiranje